Evaluation of high-yielding cardamom (Elettaria cardamomum) selections in Karnataka for yield and quality* - PRASATH, D; VENUGOPAL, M N; KUMAR, R SENTHIL (The Indian Journal of Agricultural Sciences, 2011)
Fourteen genotypes of cardamom (Elettaria cardamomum Maton) including 3 popular farmers’ selections were evaluated during 2003–07 at high altitudes to assess the yield as well as to identify the suitable genotypes under Karnataka conditions. Results indicated that in terms of yield, the farmers’ selections performed at par with the released variety ‘IISR Suvasini’. The estimated yield (dry) over 3 years varied from 524.35 kg/ha (‘APG 387’) to 1140.54 kg/ha (‘APG 250’). Among the genotypes, ‘APG 250’ and ‘APG 416’ performed consistently with higher yield in all the 3 years.